THE ROLE OF ISO 31000 RISK MANAGEMENT IN MODERATING THE INFLUENCE OF THE MANAGEMENT CONTROL SYSTEM AND LEADERSHIP STYLE ON FINANCIAL PERFORMANCE AT PT. ANGKASA PURA I AND II (PERSERO) PERIOD 2020 – 2023 - Yudhistira Saputra; Agus Ismaya Hasanudin (ZILLZELL MEDIA PRIMA, 2025)
Changing dynamic business environments require companies to optimize management control systems (SPM), leadership styles, and risk management based on ISO 31000 to maintain financial performance. This study aims to analyze: (1) the influence of SPM and leadership style on financial performance, and (2) the role of ISO 31000 risk management moderation in strengthening the relationship with contingency theory as a theoretical basis to explain the interaction between variables in the context of environmental uncertainty. The study used a quantitative method with primary data from 147 respondents taken through purposive sampling techniques. Data analysis was carried out by Moderated Regression Analysis (MRA) processed with SPSS 25 software. The results of the study showed that the Management Control System (SPM) had a significant positive effect on Financial Performance, Leadership Style had a significant positive effect on Financial Performance, ISO 31000 Risk Management moderated the relationship between the Management Control System on Financial Performance, and ISO 31000 Risk Management could not moderate the relationship between Leadership Style and Financial Performance.